Just showing is not enough: First-person-view-videos as a feedback tool in resuscitation simulation. (March 2022) - Soellner, N.; Eiberle, M.; Berberat, P.O.; Schulz, C.M.; Hinzmann, D.; Rath, S.; Haseneder, R.; Gartmeier, M.
Highlights: First-person-view videos were used as feedback tool in simulation-based resuscitation training. Giving immediate feedback using first-person-view videos was technically feasible. Participants reported positive instructional effects of first-person-view videos. Feedback with first-person-view videos showed no statistically significant improvements in simulation. Showing first-person-view videos without didactical support is not sufficient. Abstract: Theory and evidence suggest beneficial effects of integrating first-person-view (FPV) videos as a feedback method in resuscitation simulation training. However, systematic research on this instructional approach is scarce. We aimed to determine the feasibility of supplementing feedback with FPV videos for simulation-based learning and its effect on cardiopulmonary resuscitation (CPR) performance. In our randomized controlled trial conducted in a simulation-based course on CPR, each participant's FPV video was recorded using a head-mounted camera and videos were shown before post-simulation debriefing. Feasibility was tested in 27 simulated CPR scenarios randomized to FPV feedback combined with instructor-led debriefing (intervention; 14 scenarios) versus instructor-led debriefing only (control; 13 scenarios). In terms of CPR (effective compression ratio [ECR]) and team performance (Team Emergency Assessment Measure [TEAM]), improvements were observed for ECR (pre-test: 0.13 ± 0.11 vs post-test 0.19 ± 0.11) and TEAM score (pre-test: 16.6 ± 7.2 vs post-test: 25.4 ± 9.2). However, improvements did not differ significantly between intervention and control group. Course participants deemed the feedback method feasible and reported positive instructional effects. In order to make use of the potential of this promising feedback tool, we conclude that it is not sufficient to show the videos without didactical assistance.